PENGARUH TEKNOLOGI TERHADAP KEPEMILIKAN HAK KEKAYAAN INTELEKTUAL: The Influence of Technology on Intellectual Property Ownership - Rr. Aline Gratika Nugrahani (Faculty of Law, Trisakti University, 2023)
One of the impacts of rapid technological advancement is the emergence of anti-mainstream thinking. In 2015, an animal protection organization declared that Naruto, a Bornean monkey, had the right to copyright for his own selfie. As Artificial Intelligence technology developed rapidly and its performance surpassed human capabilities, it was argued that Artificial Intelligence should be entitled to Intellectual Property Rights. This paper uses normative research methods with legislative and case approaches. Based on several theories, it can be concluded that a legal subject is anything that can hold rights and obligations under the law. Technically, Artificial Intelligence can indeed perform many tasks usually done by humans, but it must be noted that Artificial Intelligence cannot enjoy its rights and fulfill its obligations. Artificial Intelligence is still a technology in the form of a computer system resulting from human innovation, not something that exists by itself. Therefore, Artificial Intelligence cannot be granted any rights, including Intellectual Property Rights, because the concept of Intellectual Property Rights is a right given to anyone who engages in intellectual activities and produces intellectual works. This right is given so that intellectual work owners can gain economic benefits, promoting the creation of sustainable Intellectual Property products.